Impacted supernumerary tooth removal by osteotomy and osteosynthesis of the anterior nasal spine - Takadoum Sarah; Favre de Thierrens Carle; Fauroux Marie-Alix (EDP Sciences, 2018)
Introduction: For dental avulsion, surgery may be invasive where it affects bone volume and may cause damage to the surrounding anatomical structures. Piezosurgery is a minimally invasive surgery due to the thin and precise cutting of the tooth compared with conventional burs. Technique: the authors have presented the case of a thirteen-year-old girl referred by her orthodontists for the extraction of a supernumerary tooth. The anterior nasal spine (ANS) was cut using piezosurgical techniques, repositioned and fixed using osteosynthesis with a bone screw. Postoperative follow ups were promising, and the bone screw was taken out a year later. Comments: The preservation of the nasal mucosa had probably aided in the trophicity and healing of ANS. The minimal bone loss by piezosurgical techniques allowed for the replacement of ANS and its osteosynthesis. Conclusion: This case describes a minimally invasive procedure which allowed for the removal of a deeply impacted supernumerary tooth, without damaging the surrounding teeth or nasal mucosa, and maintaining ANS bone volume.